2022
DOI: 10.1172/jci.insight.158030
|View full text |Cite
|
Sign up to set email alerts
|

Strong off-target antibody reactivity to malarial antigens induced by RTS,S/AS01E vaccination is associated with protection

Abstract: Conflict of interest: JJC, AR, and AO are employees of Antigen Discovery, Inc. (ADI), a company that carries patents (US Patent 10174311 and US Patent 20160320404) related to the protein array analyses used here and the location where the arrays were conducted.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Overall, our data show that the total polyclonal binding antibody titers resulting from immunization were not directly associated with sterile protection in this study. It is possible that protection is associated with specific functional antibody subsets within the polyclonal antibody mixture based on either on-target epitope specificity ( 40 ), antibody isotype ( 10 , 11 ), or off-target cross-reactivity ( 41 ). We and others had previously shown that the composition of the polyclonal antibody response can be diverse enough to include antibodies capable of inhibiting the parasite as well as those that do not have a detectable impact on the course of infection despite their ability to bind the antigen ( 24 , 42 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data show that the total polyclonal binding antibody titers resulting from immunization were not directly associated with sterile protection in this study. It is possible that protection is associated with specific functional antibody subsets within the polyclonal antibody mixture based on either on-target epitope specificity ( 40 ), antibody isotype ( 10 , 11 ), or off-target cross-reactivity ( 41 ). We and others had previously shown that the composition of the polyclonal antibody response can be diverse enough to include antibodies capable of inhibiting the parasite as well as those that do not have a detectable impact on the course of infection despite their ability to bind the antigen ( 24 , 42 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…One unexpected finding was the antibody response to CSP after infection with blood stage parasites; we hypothesize that the abundance of low complexity, highly immunogenic repeat regions shared by CSP and some blood stage antigens may have resulted in a degree of cross-reactivity ( 52 ). Unexpected blood stage antigen reactivity has been observed previously after RTS’S vaccination ( 53 ).…”
Section: Discussionmentioning
confidence: 65%
“…Overall, our data show that the total polyclonal binding Ab levels resulting from immunization were an insufficient predictor of sterile protection in this study. It is possible that protection is associated with functional antibody subsets either based on on-target epitope specificity 34 , antibody isotype 9,10 or off-target cross-reactivity 35 . We and others had previously shown that the character of the polyclonal Ab response can be diverse enough to include antibodies capable of inhibiting the parasite as well as those that don't have a detectable impact on the course of infection despite their ability to bind the antigen 22,[36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%